(untitled) (Web of Teachers: Inderscience Research, 2023)
This study delves into the structural and semantic features of phrases in the English and Uzbek languages. By comparing these two distinct language families, it explores how phrases are structured and how semantics are conveyed. English relies on word order and modifiers, while Uzbek employs an agglutinative system with suffixes and affixes. Understanding these differences is essential for effective communication and translation between these languages, emphasizing the cultural and linguistic diversity of human communication.